Effect of provenances on wood properties of Balfourodendron riedelianum - Assad, Amanda Aparecida Vianna; Ballarin, Adriano Wagner; Freitas, Miguel Luiz Menezes; Longui, Eduardo Luiz (Instituto de Ecología, A.C., 2020)
Wood is comparatively more conservative than other parts of trees, such as leaves, which present greater phenotypic plasticity. We studied the effect of seed origin on annual increment, physical-mechanical properties and anatomical characteristics of Balfourodendron riedelianum wood in a homogeneous plantation (Luiz Antônio Experimental Station (LAES)) from three natural provenances (Gália and Bauru in São Paulo State and Alvorada do Sul in Paraná State, Brazil). Because genotypic information is a determinant of wood formation, trees were expected to develop wood structure based on their provenances. Our results demostrate that variations in volume, properties and wood anatomy were influenced by provenance. Alvorada do Sul trees showed lower growth in volume and higher strength and homogeneity, compared to Gália and Bauru. Typical radial pattern was not observed for most characteristics, except modulus of elasticity and fiber length in Gália and compression parallel to the grain in Bauru that increased towards the bark. Based on the latter characteristc, B. riedelianum wood in a homogeneous planting has class C40 mechanical strength, as indicated for use in medium-sized structures, light civil construction and the manufacture of furniture.